Investigation of water-retention and uniaxial compression behaviour of MX80 bentonite pellet at various suctions - Yang Jin-Wen; Cui Yu-Jun; Mokni Nadia (E3S Web of Conferences, 2023)
MX80 bentonite pellet/powder mixture has been regarded as a candidate sealing material in deep geological high-level radioactive waste disposal. As single pellet plays an important role in the global hydromechanical behaviour of the mixture, a series of single pellet compression tests were conducted on cylindershape MX80 bentonite 32-mm pellet after reaching suction equilibrium. The changes in volume and water content during the suction equilibration with the vapour equilibrium technique allowed the water-retention properties to be investigated. X-ray μCT observations were also made on pellets after reaching the target suctions. Results showed that upon drying the water content, void ratio and volumetric strain decreased slightly, but increased significantly upon wetting. Moreover, upon drying the network of cracks presented insignificant change and the cracks were mainly located in the marginal areas of pellet, while on wetting, cracks substantially propagated from the marginal areas to the core of pellet. The uniaxial compression tests on single pellets showed that the axial strain εaxial contributed to the contractancy, while the lateral strain εlateral to the dilatancy. The uniaxial shear strength σa, max, the crack closure (CC) stress σcc, the crack initiation (CI) stress σci, the crack damage (CD) stress σcd and the Young’s modulus E were found to decrease with suction decreasing, evidencing the suction effect through softening and cracking. Because of the combined effect of suction and wetting-induced cracks, the Poisson’s ratios v increased until the suction decreased to 38-25 MPa, and then decreased with further suction decrease. Uniaxial loading closed the horizontal wetting-induced cracks at suctions ≤ 9 MPa, leading to a drop of εlateral before CC.